ANALISISPENGARUH ARUS KAS OPERASI DAN ARUS KAS INVESTASI TERHADAP PROFITABILITAS PERUSAHAANPADA PT MULTI SUKSES - Tuti Fitriani; Abu Bakar (JURNAL ULET (Utility, Earning and Tax), 2019)
This study aims to determine the effect of cash flow from operating activities and cash flows on investment activities on the profitability of the company in PT Multi Sukses. In this study the cash flow of operating activities is represented by the cash flow liquidity ratio, and the cash flow of investment activities is represented by the cash flow investment ratio. The researcher uses an associative approach, where the associative approach aims to determine the effect of operating cash flows and investment cash flows on the profitability of the company. Data collection is done by documentation and library engineering techniques. The results showed that the operating cash flow diproxy of cash flow liquidity ratios had a significant effect on the profitability of the company while the investment cash flow proxy from the cash flow investment ratio had no significant effect on the profitability of the company.